Evaluation of water use efficiency in irrigated agriculture supported by satellite images - Palacios-Vélez, Enrique; Espinosa-Espinosa, José L.; Palacios-Sánchez, Luis A. (Tecnología y ciencias del agua, 2018)
Palacios-Vélez, E., Palacios-Sánchez, L. A., & Espinosa- Espinosa, J. L. January-February, 2018). Evaluation of water use efficiency in irrigated agriculture supported by satellite images. Water Technology and Sciences (in Spanish), 9(1), 31- 38, DOI: 10.24850/j-tyca-2018-01-02. Â Â Â Â Â To evaluate the water use efficiency is a necessary condition to improve water productivity. The overall water use efficiency is the product of conveyance efficiency in the largest and minor irrigation canal systems, multiplied by the application efficiency at the usersÂ´ plots. Conveyance efficiency is achieved by measuring the water delivered at the irrigated plots between the amounts of water taken from the sources of supply. These measurements are generally carried out by the personnel operating the irrigation systems. In most of the districts, these measurements are usually carried mandatory to report to the National Water Commission, with a variable precision. However, the water application efficiency in the usersÂ´ plots is much more difficult to be done, because the measurement of water consumption by plants is not easy to assess. Indeed, the efficiency in plot irrigation, is the ratio of crop water evapotranspiration between the amounts of water applied, both measurements are difficult to perform. However, in recent years it has been possible to estimate water consumption by crops using satellite imagery. Thus, in this paper, a methodology used in the Mayo River Irrigation District in Sonora, Mexico is shown for the last agricultural cycle 2015-2016 using Landsat 7 and 8 satellite images, with acceptable results. This methodology is based on the PLEIADES project 2007 â€“ 2010. Â Â